Meta-analysis and Systematic Review of Skin Graft Donor-site Dressings with Future Guidelines - Arman T. Serebrakian, MD, MS; Brent B. Pickrell, MD; David E. Varon, BA; Amin Mohamadi, MD, MPH; Mark W. Grinstaff, PhD; Edward K. Rodriguez, MD, PhD; Ara Nazarian, DrSc; Eric G. Halvorson, MD; Indranil Sinha, MD (Plastic and Reconstructive Surgery, Global Open, 2018)
Background:. Many types of split-thickness skin graft (STSG) donor-site dressings are available with little consensus from the literature on the optimal dressing type. The purpose of this systematic review was to analyze the most recent outcomes regarding moist and nonmoist dressings for STSG donor sites. Methods:. A comprehensive systematic review was conducted across PubMed/MEDLINE, EMBASE, and Cochrane Library databases to search for comparative studies evaluating different STSG donor-site dressings in adult subjects published between 2008 and 2017. The quality of randomized controlled trials was assessed using the Jadad scale. Data were collected on donor-site pain, rate of epithelialization, infection rate, cosmetic appearance, and cost. Meta-analysis was performed for reported pain scores. Results:. A total of 41 articles were included comparing 44 dressings. Selected studies included analysis of donor-site pain (36 of 41 articles), rate of epithelialization (38 of 41), infection rate (25 of 41), cosmetic appearance (20 of 41), and cost (10 of 41). Meta-analysis revealed moist dressings result in lower pain (pooled effect size = 1.44). A majority of articles (73%) reported better reepithelialization rates with moist dressings. Conclusion:. The literature on STSG donor-site dressings has not yet identified an ideal dressing. Although moist dressings provide superior outcomes with regard to pain control and wound healing, there continues to be a lack of standardization. The increasing commercial availability and marketing of novel dressings necessitates the development of standardized research protocols to design better comparison studies and assess true efficacy.